Re-evaluating Albendazole-Based Preventive Chemotherapy for Soil-Transmitted Helminths in Indonesia: A Narrative Review on Efficacy, Challenges, and Future Strategies - Lala Gunasari; Dian Nurmansyah; Dessy Triana (Sciences and Clinical Pharmacy Research Journal, 2026)
This narrative review seeks to critically analyze the efficacy of albendazole, the cornerstone anthelmintic of the program. Relevant literature (2020-2025) was identified through a systematic search of the ScienceDirect and Google Scholar databases. While evidence confirms albendazole's effectiveness, with cure rates up to 93%, its performance is inconsistent and influenced by a confluence of factors. A critical constraint identified is the absence of robust, large-scale national surveillance data on STH prevalence and drug efficacy, hindering a comprehensive assessment of albendazole's performance within the program. The persistent burden of STH underscores a gap between program implementation and its intended public health impact. While albendazole remains essential, its variable efficacy and operational barriers necessitate a critical reassessment of the current strategy.